Perancangan Sistem Informasi Pengaduan RSUD Dr.Soedarsono Pasuruan Berbasis Website Dengan Menggunakan Metode Waterfall: Bahasa Indonesia - Nirma Dwi Wulansari Nirma; Gita Indah Marthasari; Briansyah Setyo Wiyono (Universitas Muhammadiyah Malang, 2023)
This research is the development of a website-based information system on complaints from RSUD dr.R.Soedarsono, Pasuruan City. Complaints in hospitals are still done manually, so far, complaints are only made face to face and using a suggestion box, where the patient must write and go to the hospital first to give advice, of course this is very impractical. This study aims to produce a system design that can help solve problems in the hospital complaint system which is still done manually, so that it is often lost or errors in inputting data are still not tracked properly, this is important to do so that it can be handled properly and can also make it easier for the public to send criticism and suggestions for hospital services that can be accessed online. The concept used in making this website applies the concept of Electronic Customer Relationship Management (E-CRM) with the method used in making this application is the waterfall model Software Development Life (SDLC) software development method. This method has several stages, namely analysis, design, implementation, testing and maintenance. It is called a waterfall because the stages that are passed must wait for the completion of the previous stage and run sequentially. System testing using Black Box Testing and User Acceptance Test (UAT). The results of the research contained in the design of the complaint information system at the dr.R.Soedarsono Hospital, Pasuruan City, were able to provide information that could be accessed anywhere and anytime and also made it easier for patients to send criticism and suggestions online.